Ethnobotanical Survey on Antidiabetic Medicinal Plants in Western Algeria: Traditional Knowledge and Public Health Implications - Chelli, Nadia; Bouabsa, Foufa; Benfreha, Hamida; Touil, Aicha Tir; Meddah, Boumediene (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: Type 2 diabetes is a global health challenge with significant socio-economic impacts, particularly in Algeria. Medicinal plants offer an affordable and accessible alternative to pharmaceutical treatments. This study aims to survey antidiabetic medicinal plants in western Algeria. Materials and Methods: The survey covered several provinces and targeted three respondent categories: herbalists, traditional healers, and phytotherapists. Data were collected through structured questionnaires, capturing information on respondent demographics and medicinal plants used for diabetes treatment. Antidiabetic plants were identified and classified, and their use-values were calculated. Results: Among the 200 participants, 90% were herbalists and traditional healers, predominantly aged 40 to 85, who had extensive knowledge of antidiabetic plants due to accumulated experience and the oral transmission of traditional knowledge. Seventy one percent (71%) of respondents were married and often responsible for providing initial therapeutic care for their families. The study identified 90 medicinal plants belonging to 21 families, with Asteraceae and Lamiaceae being the most represented (10%). Leaves were the most commonly used plant part (42.50%), followed by seeds (15.30%) and fruits (8.21%). Decoction and infusion were the primary preparation methods (31.28% and 46.93%), respectively. Finally, Trigonella foenum-graecum, Berberis vulgaris, Centaurium erythraea, Artemisia herba-alba Asso, Zygophyllum album L., Citrullus colocynthis (L.), Olea europaea, Rosmarinus officinalis, Tetraclinis articulata, Cinnamomum verum and Ajuga iva (L.) were the most frequently cited plants, with use values (UV) ranging from 0.245 to 0.09, respectively. Conclusion: This study highlights the value of traditional medicinal plants in diabetes management in western Algeria, emphasizing the need for pharmacological studies and dosage standardization to ensure safe and effective use.
Keywords: Ethnobotanical Study; Type 2 Diabetes; Western Algeria; Medicinal Plants; Traditional; Knowledge